Pieces of a girl - Kuehnert, Stephanie, 1979- (Dutton, an imprint of Penguin Random House LLC, 2024)
"Pieces of a Girl is a memoir about abuse and addiction and the power of storytelling and community that helped zine creator and novelist Stephanie Kuehnert survive and thrive. Told in journal entries, original illustrations, and pages torn from her actual diaries and zines, this is the story of Stephanie's life as a struggling outsider who survived substance and relationship abuse to beocme a strong young woman after years trapped in a cycle that sometimes seemed to have no escape." --